Green Experience and Digital Engagement as Drivers of Generation Z Consumer Loyalty in Coffee Shops: A Mediation Model of Perceived Value and Brand Attachment - Mahardika Agung Madepo; Lina Budiarti; Romi Ferdian; Lidya Verawati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The increasing adoption of sustainable practices and digital technologies has reshaped consumer behavior, particularly among Generation Z coffee shop customers. This study examines the effects of green experience and digital engagement on Generation Z consumer loyalty through the mediating roles of perceived value and brand attachment. A quantitative survey was conducted among 300 Generation Z coffee shop customers in Pontianak, Indonesia. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that green experience significantly enhances perceived value (β = 0.728, p < 0.001), while digital engagement positively influences brand attachment (β = 0.799, p < 0.001). Perceived value emerged as the strongest predictor of consumer loyalty (β = 1.491, p < 0.001), followed by brand attachment (β = 0.089, p < 0.001). Furthermore, perceived value and brand attachment significantly mediate the relationships between green experience, digital engagement, and consumer loyalty. These findings demonstrate that Generation Z consumer loyalty is primarily developed through cognitive evaluations and emotional attachment. The study provides theoretical insights into sustainable consumer behavior and offers practical guidance for coffee shop managers in developing sustainability-oriented and digitally engaging strategies to strengthen long-term consumer loyalty.